The The Effect of The Board of Commissioners, Audit Committee and Sharia Supervisory Board on Disclosure of Islamic Social Reporting in Sharia Banking in Indonesia - Qur'Ani , Fiar Hening; Husnul Khotimah (Adpebi Science Series, 2024)
This study aims to examine the effect of the Board of Commissioners, Audit Committee and Sharia Supervisory Board on the disclosure of Islamic Social Reporting (ISR) at Islamic Commercial Banks in Indonesia in 2015 - 2020. Hypothesis testing is carried out using panel data regression analysis . The results showed that the Board of Commissioners had no significant effect on Islamic Social Reporting (ISR). While the Audit Committee and Sharia Supervisory Board have a positive and significant impact on Islamic Social Reporting (ISR). The results of this study indicate that good corporate governance is very important for the disclosure of information on Islamic Social Reporting at Islamic Commercial Banks.